Operational efficiency and environmental impacts: a study on cut-to-length logging in the Carpathian forests - Allman, Michal; Jankovský, Martin; Bobrík, Vladimír; Dudáková, Zuzana (Frontiers in Forests and Global Change, 2025)
IntroductionThe performance and consumption of CTL technologies in the forest harvesting process are influenced by a wide range of technological conditions and factors, requiring detailed analysis to increase machine performance and reduce environmental impacts.MethodsIn the presented study, we investigated the efficiency of different CTL (cut-to-length) logging machines in 1,390 forest stands from 2020 to 2022. We focused on analyzing variables that substantially affect machine productivity, fuel consumption, and the resulting CO2 emissions of harvesters and forwarders. Utilizing data from 4,044 work shifts, we determined the effect sizes and order of the variables in terms of their effects on productivity and fuel consumption. We used linear mixed models, one-way ANOVA, and regression and correlation analyses.ResultsOur findings revealed fuel consumption rates ranging from 2.65 to 2.95 liters per cubic meter of timber, directly influencing CO2 emissions, estimated between 7.11 and 7.91 kilograms per cubic meter of timber. Linear Mixed Models showed a significant effect (p<0.05) of the mean volume of the harvested trees (m3), duration of downtime, and other variables on the productivity of the CTL machines. Regression and correlation analyses showed a significant relationship (p<0.05) between variables: fuel consumption (l), mean productivity (m3), number of days worked, and number of down days, which have a substantial effect on CO2 emissions.ConclusionThis study sheds light on the carbon emissions of modern forestry technologies and underscores the critical importance of optimizing logging operations to reduce them.